Faktor-Faktor Yang Mempengaruhi Loyalitas Pelanggan Pada Akomodasi Penginapan Traveloka - Elleta Sheldi Aranda (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Every year, the internet and technology continue to evolve and advance. Data indicates that Indonesia, with 170.4 million smartphone users, is in fourth place in 2020. It is also reinforced by the entirely digital world that exists today, which necessitates that everyone own a smartphone. One of the nations with the highest smartphone penetration rates worldwide is Indonesia. There are now 61.7 percent of people in the nation who own smartphones. The purpose of this study was to determine what aspects of Traveloka hotels affect patron loyalty. Self-gratification value, social value, customer satisfaction, and revisit intention are other variables that were used in this study. The Indonesians who have booked hotels through the Traveloka app are the study's target group. Based on the data that has been obtained through online questionnaires, this study managed to collect as many as 521 respondents. Analyzed using the partial least square-structural equation modeling approach on SmartPLS. Based on this, it shows that the variables in this study have a positive influence on customer loyalty using the Traveloka application as accommodation accommodation.